Updates on the etiopathogenic mechanisms that promote endometriosis-associated infertility: a literature review (Research, Society and Development, 2023)
Introduction: Today, it is known that endometriosis is a chronic gynecological disease, of an inflammatory nature, marked by the presence of endometrial tissue outside the uterus (ectopic), dependent on estrogen. Endometriosis can be classified as superficial, ovarian and deep, in addition to extrapelvic and is mainly marked by dyspareunia, dysmenorrhea, dysuria, dyschezia and infertility (a challenge for 30 to 50% of these women). Objective: To identify the etiopathogenic mechanisms that could explain the prevalence of infertility in women with endometriosis. Materials and Methods: This is an integrative literature review about the new evidence that justifies infertility in women with endometriosis. The PICO strategy was used to prepare the guiding question. In addition, the descriptors “endometriosis”, “infertility”, “pathogenesis” and “etiology” were crossed in the databases National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Google Scholar and Biblioteca Virtual Health (VHL). Results and Discussion: The environment provided by endometriosis promotes several changes, including: the high inflammatory character, cytokine imbalance, oxidative stress and changes in follicular and peritoneal fluid. The immune system seems to be impaired, with changes in the function of most immune cells. Hormonal imbalance, genetic and epigenetic factors are also fundamental. Conclusion: The association between infertility and endometriosis seems to impair conception due to changes in follicular fluid and folliculogenesis, reduced oocyte quality, changes in implantation window, sperm changes and ciliary cell dysfunction.